2000
DOI: 10.1212/wnl.54.6.1277
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities in mobility-impaired older persons

Abstract: This cross-sectional study suggests that decreased white matter volume is age-related, whereas increased white matter signal abnormalities are most likely to occur as a result of disease. Both of these changes are independently associated with impaired mobility in older persons and therefore likely to be additive factors of motor disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
108
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 41 publications
(28 reference statements)
10
108
4
Order By: Relevance
“…6,16,42 Few cross-sectional studies reported a correlation between the extent of LA evaluated visually or with computation of LA volume and gait or motor deficit. 8,11,12,16 We failed to identify any correlation between the extent of LA and clinical scores of motor or cognitive deficit in our small cross-sectional study. This confirms that visual scales are not very sensitive to the clinical counterpart of LA.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…6,16,42 Few cross-sectional studies reported a correlation between the extent of LA evaluated visually or with computation of LA volume and gait or motor deficit. 8,11,12,16 We failed to identify any correlation between the extent of LA and clinical scores of motor or cognitive deficit in our small cross-sectional study. This confirms that visual scales are not very sensitive to the clinical counterpart of LA.…”
Section: Discussioncontrasting
confidence: 55%
“…3,4 The possible correlation of LA with cognitive decline or motor deficit has been investigated using visual or computerized methods to assess the LA extent. [5][6][7][8][9][10][11][12][13][14][15][16] Diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) are MR techniques sensitive to changes in the diffusion properties of water protons in terms of apparent diffusion coefficient (ADC), mean diffusivity (MD), or fractional anisotropy (FA). Previous studies using region of interest measurements have demonstrated that MD and FA in patients with LA are altered not only in the areas exhibiting signal intensity changes in T2-weighted images but also in the normal-appearing white matter.…”
mentioning
confidence: 99%
“…To our knowledge, this has not been previously demonstrated. Nevertheless, it does concur with observations that show covert white matter lesions are associated with impaired mobility (Guttmann et al 2000;Benson et al 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Using this approach, significant correlations have been noted between neuroimaging-derived measures of white matter integrity and ventricle size with aspects of body sway (Tell et al, 1998;Guttmann et al, 2000;Starr et al, 2003;Sullivan et al, 2009). For example, with respect to aging, Sullivan et al (2009) recently showed that sulcal/ventricular enlargement and increased white matter hyperintensities predicted increased body sway during stand- ing.…”
Section: Discussionmentioning
confidence: 99%